Biochemical and hematological factors associated with COVID-19 severity among Gabonese patients: A retrospective cohort study - N’dilimabaka, Nadine; Mounguegui, Dieudonné Mounguegui; Lekana-Douki, Sonia Etenna; Yattara, Marisca Kandet; Obame-Nkoghe, Judicaël; Longo-Pendy, Neil Michel; Koumba, Ingrid Precilya Koumba; Mve-Ella, Octavie Lauris Banga; Moukouama, Schedy Koumba; Dzembo, Cresh Emelya; Bolo, Lauriane Yacka; Biyie-Bi-Ngoghe, Prudence; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The COVID-19 disease presents a large range of clinical manifestations and includes asymptomatic, mild, and severe cases. The level of severity is related to parameters associated with immunity, genetics, and biochemistry. Africa shows one of the lowest COVID-19 fatality rates but very few data on the biochemical markers of COVID-19 in patients and the factors associated with disease severity are available for the continent. In Gabon, the COVID-19 fatality rate is only 0.63% but almost no data on biomarkers in COVID-19 patients have been published. Both the number of COVID-19 cases and the mortality rate reported in Africa in general, and in Gabon in particular, are lower than in non-African countries. As such, understanding the factors associated with disease severity in Gabonese patients is a crucial step to better understand the disease in the African context and prepare for future COVID-19 waves and other epidemics of emerging diseases. Here, we compared biochemical and hematological markers among 753 Gabonese COVID-19 patients with asymptomatic (184/753), mild/moderate (420/753), and severe/critical (149/753) forms of the disease using an Analysis of Variance (ANOVA) or a Kruskal-Wallis (KW) test. We modeled these parameters together with comorbidities, age, and sex to predict factors associated with disease severity by using a "binomial generalized linear model" utilizing the "package" stats of R software version 4.0.2. Our results showed that almost all the biochemical and hematological parameters (except creatinine, phosphorus, D-dimers, platelets, and monocytes) varied according to disease severity. However, age and the dysfunction of organs like the kidney, liver, and lung together with the decrease of electrolytes (chloride, potassium, and sodium) are the best predictors of disease severity in Gabonese patients.